PATRIARCHAL SOCIETY AND WOMEN’S POSITION IN ACTION MOVIE GENRE: CASE STUDY OF PIERRE MOREL’S TAKEN (EUFONI: Journal of Language, Literary, and Cultural Studies, 2018)
Action movie has established itself as one of the leading movie genres which has been present in the film industry for a long time. However, action movie genre has been characterized as male-oriented. This study aims to reveal the issue of patriarchal society and women's position represented in action movie entitled Taken, directed by Pierre Morel. Research problems in this study are related to: (a) how is the superiority of men depicted in the movie, and (b) how is women represented as the secondary subject. To analyze the movie, this study used the theory of Simone de Beauvoir especially in her book, The Second Sex. The result of this study showed that Taken movie reproduce the stereotype of action movie genre as male-oriented and women is considered as the secondary subject.Keywords: Taken, Action Movie Genre, Patriarchal Society, Secondary Subject, Simone de Beauvoir.